2004
DOI: 10.1089/088318704322994967
|View full text |Cite
|
Sign up to set email alerts
|

The High Prevalence of Rhinitis, Rhinoconjunctivitis, and Eczema in Costa Rican Schoolchildren Studied with the ISAAC Protocol

Abstract: The aim of our study was to estimate the prevalence and severity of allergic rhinitis, rhinoconjunctivitis, and eczema in Costa Rican schoolchildren. We have reported asthma prevalence in the same cohort elsewhere. A questionnaire based survey was conducted on a random sample of children (n 5 6144), aged 6-7 years and 13-14 years from 75 educational centers throughout Costa Rica, using the International Study of Asthma and Allergies in Childhood (ISAAC) protocol. The prevalence in the 6-to 7-year-old group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The majority of the studies recruited children from an urban background. Fourteen studies assessed both children (aged around 6-7 years) and adolescents (aged around 13-14 years), and provided the prevalence stratified by age [9,18,19,20,21,22,23,24,25,26,27,28,29,30]. …”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies recruited children from an urban background. Fourteen studies assessed both children (aged around 6-7 years) and adolescents (aged around 13-14 years), and provided the prevalence stratified by age [9,18,19,20,21,22,23,24,25,26,27,28,29,30]. …”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported the burden of AR/ARC or SAR on daily activities in adolescents. 18,22,31,36,41 All demonstrated that AR/ARC or SAR had some effect on daily functioning (Table 2). A real-world observational study that used the Work-Productivity and Activity Impairment-Allergy-Specific (WPAI-AS) questionnaire showed activity impairment in French adolescents (aged 12-17 years) with SAR, which worsened with increasing symptom severity.…”
Section: Burden On Daily Activitiesmentioning
confidence: 98%
“…18 Three studies conducted in Malta, Costa Rica, and South Africa used the standard ISAAC questionnaire to elicit information on daily activities, and all reported a moderate-to-severe effect as a result of AR/ARC in adolescents (aged 13-15 years). 31,36,41…”
Section: Burden On Daily Activitiesmentioning
confidence: 99%